Exploring the overlap between individualistic and collective crime prevention. Issue 4 (November 2016) - Madero-Hernandez, Arelys; Fisher, Bonnie; Wilcox, Pamela
Abstract Crime prevention behaviors range from private-minded or individualistic actions citizens take to protect themselves from crime, to public-minded or collective behaviors aimed at protecting entire neighborhoods. Although these behaviors may be overlapping, few studies have examined the extent to which citizens engage in individualistic and collective crime prevention simultaneously. This study examines the co-occurrence and predictors of crime prevention behaviors with data from Canada's General Social Survey. Results indicate that citizens who engage in individualistic crime prevention behaviors are somewhat likely to engage in collective ones. But when looking at the etiology of these behaviors, individualistic behaviors are largely influenced by concerns about victimization, while collective behaviors are driven more by concerns with neighborhood conditions.